SIFAT LISTRIK DAN MAGNETIK LAPISAN TIPIS NANOKOMPOSIT Fe-C/Si(100)[Electrical and Magnetic Properties of Fe-C/Si(100) Nanocomposite Thin Film.] - Yunasfi, Yunasfi; Mashadi; Yusuf, Saeful (Jurnal Metalurgi, 2013)
Characterization of electrical and magnetic properties of Fe-C/Si(100) nano composite thin film were carried out. Carbon nanocomposite and nanostructured with containing iron nanoparticles exhibit electrical and magnetic properties, so a lot of the electromagnetic field is applied in the form of thin layers. The purpose of this study was to observe the electrical and magnetic properties of Fe-C/Si (100) nanocomposite thin layer in the context of its application in the field of sensors. Fe-C nanocomposites were made by mixing graphite and Fe in various weight % of Fe (1 - 3 weight %) using High Energy Milling (HEM) for 50 hours. After mixing powder of Fe-C were compacted by pressing machine, the pellets were used as a sputtering target for growth of Fe-C nanocomposite thin film on Si(100) substrate. The result observation of SEM shows that the thin film has flat and smooth surface, particle of Fe-C was clearly and homogenously deposited on Si(100) with the particle size of around 50 nm. From cross section observation, it is shown that the graphite thin film has been formed on Si(100) substrate with a thickness of around 100 nm. Characterization of electrical property using LCR meter shows that the conductance value of Fe-C/Si(100) become higher in accordance with the increasing of Fe. Characterization of magnetic property using Four Point Probe method shows that the Fe- C/Si(100) thin film is a positive magnetoresistance, which in accordance with the increasing of Fe inside the Fe-C thin film, the resistivity value become lower and the MR value become higher.